Formation of some elements of the right to defence in misdemeanour proceedings (Ius Novum, 2024)
The text is an analysis of the normative solutions concerning the right to defence in Polish proceedings in cases of offences. It discusses the formation of selected elements of the right to defence, starting from the pre-war solutions until modern times. The author points out the autonomy of the solutions in force in the 2001 Code of Proceedings in Misdemeanour Cases, but also their similarities to the right to defence in criminal cases, which constitutes the most comprehensive model of this right.
Keywords: defence, defendant, defence counsel, procedural guarantees, offenders, misdemeanour proceedings, criminal proceedings